Aggressive Management Model in Schizophrenic Patients: A Systematic Review - Maming, Bukhori; Kongsuwan, Vineekarn (Princess of Naradhiwas University Journal, 2023)
The propose of this systematic review was to study Aggressive Management Model (AMM) in schizophrenic patients by analyzing and synthesizing of concepts, patterns, and outcomes that reduce aggressive behavior. Research articles were retrieved from the following database: CINAHL, PubMed, ProQuest, ThaiJO, TDC-ThaiLIS and Google Scholar from 2012-2021. The research data were analyzed using summaries of articles and synthesized by using the criteria of The Joanna Briggs Institute (2014). There were 10 selected articles (n=10) related to action research, research and development, quasi-experimental research, and experimental research. The results of analysis revealed that there were 6 concepts used as a framework for constructing AMM: 1) Anger Management 2) Self-management 3) Mindfulness Based Cognitive Therapy 4) Cognitive and Behavior Adjustment Therapy 5) Assertive Training: Role-Playing, and 6) Muscle relaxation. Moreover, there were others 5 related concepts included with 1) Peplau's Interpersonal Relations Theory 2) Psychoeducation Group 3) Motivational Enhancement 4) Stress Management, and 5) Mental Strength. The results of the study found that a pattern of AMM was the operation of group activity which were self-recognition and awareness, feelings, and emotions that lead to aggressive behavior, skills training for assertiveness, and application in daily life. The majority of program activities’ duration was 60-90 minutes each time from 1-4 weeks. The outcomes of applying AMM were the aggressive behavior of patients has decreased, the emotional confrontation and expression was coped up more appropriately, and the happiness of life was increased. These models or programs can be utilized in clinics in order to reduce aggressive behavior in schizophrenic patients.